Histological responses of golden apple snail (Pomacea canaliculata) to copper - Pena, Silvia C.; Pocsidio, Glorina N.; Co, Elisa L. (2017)
Histopathological changes in kidney, digestive gland, foot, and gills of Pomacea canaliculata due to copper exposure were studied to assess copper?s effects on tissues of its different organs and also for the possibility of being used as a biomarker. Three-month-old snails were exposed to copper (67.5µg L-1) for seven days and were excised and fixed in 10% formalin. Routine histological preparation and examination exhibited varied forms and degrees of aberrations. These include hydropic degeneration, disintegration and loss of cells, elongation of kidney tubules, hyperplasia of K corpuscles in the digestive gland, flattened epithelium, and muscular bundles in foot in complete disarray, dilations and folding of the gill filaments. Gross and subtle tissue alterations in these organs may lend support to the role of P. canaliculata as a biomarker for copper contamination. (Author's abstract)